2008
DOI: 10.3171/jns.2008.109.12.1113
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular ultrasonography-guided stent angioplasty of an extracranial vertebral artery dissection

Abstract: The authors report on a case of intravascular ultrasonography (IVUS)-guided stent angioplasty for iatrogenic extracranial vertebral artery (VA) dissection in a 49-year-old man after coil embolization for an unruptured aneurysm of the right posterior inferior cerebellar artery. Insignificant dissections occurred during the procedure. Postoperatively, the patient experienced gradually worsening posterior neck pain and headache, and follow-up angiography 8 months after the coil embolization revealed expansion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…26) IVUS-guided stent angioplasty of an extracranial vertebral artery dissection was valuable for understanding the intravascular environment, confirming the true lumen, and evaluating stent apposition. 25) Intracranial IVUS remains challenging, and requires a device with high trackability to overcome the tortuous and long pathway to the target. More low-profile devices with better trackability are essential for further refinement of the technique.…”
Section: Discussionmentioning
confidence: 99%
“…26) IVUS-guided stent angioplasty of an extracranial vertebral artery dissection was valuable for understanding the intravascular environment, confirming the true lumen, and evaluating stent apposition. 25) Intracranial IVUS remains challenging, and requires a device with high trackability to overcome the tortuous and long pathway to the target. More low-profile devices with better trackability are essential for further refinement of the technique.…”
Section: Discussionmentioning
confidence: 99%
“…13 One case report demonstrated the feasibility and safety of intravascular sonographyϪguided stent angioplasty of an iatrogenic extracranial vertebral artery dissection. 87 Takayama et al 88 also did not encounter any complications during the virtual histology intravascular sonography evaluation of a symptomatic intracranial right vertebral artery stenosis. Similarly, Wehman et al 9 demonstrated that the intravascular sonography mapping of a basilar artery stenosis can be safely performed.…”
Section: Safety Of Intravascular Sonographymentioning
confidence: 99%
“…With the conventional intravascular data, the vessel media diameter was found to be 5.9 ϫ 6 mm. 87 The plaque components were identified through the virtual histology analysis: fibrous (72%), fibrofatty (17%), necrotic core (7%), and attenuated calcium (4%) components. 87 Virtual histology intravascular sonography demonstrated the ability to identify a stable plaque and provide a better estimate of the size of the balloon-expandable stent needed for treatment.…”
Section: Intracranial Application Of Intravascular Sonographymentioning
confidence: 99%
See 2 more Smart Citations